2013
DOI: 10.3109/00365513.2013.794300
|View full text |Cite
|
Sign up to set email alerts
|

Strong negative interference of ethamsylate (Dicynone®) in serum creatinine quantification via enzymatic assay using Trinder reaction

Abstract: Considering the strong negative interference of ethamsylate in enzymatic assay using Trinder reaction for creatinine quantification, blood from patients with prescribed Dicynone should be taken at least 12 h after the last application of the drug for obtaining the correct creatinine values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…This approach more objectively reflects the presence of interference than those using the alkaline picrate method, as previously compared in the other study. 5 Second, blood concentrations of calcium dobesilate in healthy participants and patients were measured, which would have consolidated our results of dose-dependent deviations in Cr levels. However, certain limitations were still present in our analyses and include a relatively small sample size and a significant age difference between healthy participants and hospitalized patients, which may influence the results.…”
Section: Discussionmentioning
confidence: 54%
“…This approach more objectively reflects the presence of interference than those using the alkaline picrate method, as previously compared in the other study. 5 Second, blood concentrations of calcium dobesilate in healthy participants and patients were measured, which would have consolidated our results of dose-dependent deviations in Cr levels. However, certain limitations were still present in our analyses and include a relatively small sample size and a significant age difference between healthy participants and hospitalized patients, which may influence the results.…”
Section: Discussionmentioning
confidence: 54%
“…Drug laboratory test interactions (DLTIs) are one of the major sources of laboratory errors, and it is necessary to strengthen the publicity and education of drug interference and enhance the attention of doctors and patients to drug interference on blood tests 16 . In addition to the calcium dobesilate highlighted in this article, there are also ethamsylate, phenolic sulfoethylamine, acetaminophen, ascorbic acid, catecholamine, aspirin, dopamine, analgin, and rifampicin detection inferenced by color development 17‐20 . Trinder's reaction involves not only creatinine but also uric acid (UA), triglyceride (TG), cholesterol (TC), high‐density lipoprotein cholesterol (HDL‐C), low‐density lipoprotein cholesterol (LDL‐C), etc 13,21 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have reported on calcium dobesilate's interference with creatinine detection based on the Trinder reaction. 13,[15][16][17] Because this reaction interferes with creatinine quantification, this is very detrimental to the evaluation of renal function, and the detection result is lower than the actual result due to negative interference. 15 This can be interpreted as the patient's kidney function is improving or that the medication is responding, thus leading to a clinical misjudgment.…”
Section: Discussionmentioning
confidence: 99%
“…For the remaining samples, the observed differences may be partially attributable to systemic differences between different reagents or other unknown interference factors in the serum samples. A number of substances may interfere with creatinine quanti cation using enzymatic assays [24][25][26][27][28][29]. For some patients with large deviating Cr-R and Cr-C assay results who did not have detectable serum CaD, we evaluated the patient's medical records and compared the creatinine levels with those determined by the reference method and identi ed ten cases where this discrepancy may have been caused by the presence of etamsylate.…”
Section: Discussionmentioning
confidence: 99%
“…For some patients with large deviating Cr-R and Cr-C assay results who did not have detectable serum CaD, we evaluated the patient's medical records and compared the creatinine levels with those determined by the reference method and identi ed ten cases where this discrepancy may have been caused by the presence of etamsylate. Etamsylate is known to interfere with enzymatic creatinine assays [28][29]. The Cr-R assay also solved the problem of interference by etamsylate, and generally gave more accurate serum creatinine results in these cases.…”
Section: Discussionmentioning
confidence: 99%